PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING BERBANTUAN CANVA DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 12 MANURUNGE - Wahyuni, Wiani; Firdaus; Sabir, Achmad (MACCA : Science-Edu Journal, 2025)
This research is classroom action research which aims to determine descriptions of teacher activities, student activities, and learning outcomes in implementing the Canva-Assisted CTL learning model in Improving Mathematics Learning Outcomes for grade IV students at SD Negeri 12 Manurunge. The subjects in this research were all 23 grade IV students and the homeroom teachers. Data collection techniques use were observation and tests. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The research results showed that teacher activities in managing learning experienced an increase in the optimal learning process from cycle I to cycle II seen from teacher activities in implementing good learning designs in accordance with the steps of the CTL learning model assisted by Canva. Student activity in participating in the learning process has increased from cycle I to cycle II as seen from the results of observations during the learning process using observation sheets. As for student learning outcomes in cycle I, there were 16 out of 23 students who completed with an average score of 79.1 with the percentage of student learning completeness reaching 69.57% (sufficient), while student learning outcomes in cycle II were 20 out of 23 students achieving a score. completed with an average score of 87.6 with a student learning completion percentage reaching 86.9% (good). It can be concluded that the Canva-assisted CTL learning model can improve student Mathematics learning outcomes.